2000
DOI: 10.2307/177408
|View full text |Cite
|
Sign up to set email alerts
|

Testing Generalities in the Shape of Patch Occupancy Frequency Distributions

Abstract: Abstract. Bimodal patch occupancy frequency distributions regularly appear in studies of a variety of taxa at a variety of spatial scales. Metapopulation models associated with the core-satellite hypothesis and a strong rescue effect predict the occurrence of this bimodality. However, there have been numerous other explanations, both artifactual and biological, of bimodality in patch occupancy frequency distributions. One approach to a better understanding of the phenomenon is to conduct studies on a variety o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
31
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 23 publications
3
31
1
Order By: Relevance
“…For instance, Collins & Glenn (1997) demonstrated that such patterns depend on the aerial extent of the study (i.e. distance scaling; see van Rensburg et al 2000 for changes in species frequency distribution between patch types). This may also apply to patterns in species frequency distribution when comparing engineered and non-engineered habitats (hereafter referred to as habitat scaling).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Collins & Glenn (1997) demonstrated that such patterns depend on the aerial extent of the study (i.e. distance scaling; see van Rensburg et al 2000 for changes in species frequency distribution between patch types). This may also apply to patterns in species frequency distribution when comparing engineered and non-engineered habitats (hereafter referred to as habitat scaling).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, at least three recent studies (Guo et al ., 2000;Van Rensburg et al ., 2000;Perelman et al ., 2001) have referred to the incorrect equation in Collins & Glenn (1997). Applying the correct equation to the data of Van Rensburg et al .…”
Section: A Typing Error In Tokeshi's Test Of Bimodalitymentioning
confidence: 99%
“…Sand Forest is part of the Tropical Dry Forest group, which is found in Maputaland (Licuati Sand Forest) and in some parts of the Kruger National Park in South Africa (Nwambyia Sand Forest) (Mucina & Rutherford 2006). The conservation of forests in South Africa is difficult because their distribution is patchy, and therefore large networks of interconnected patches are needed to conserve their species diversity and dynamics (Midgley et al 1990;Everard et al 1994;Everard et al 1995;Low & Rebelo 1998;Van Rensburg et al 2000b;Lawes et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The phytogeographic affinities and similarities of Sand Forest with Afromontane and Coastal forests (Van Rensburg et al 1999;Matthews et al 2001) suggest that Sand Forest may be a relict of previous climatic conditions . Many authors agree that under the current climatic conditions, Sand Forest may be transformed into woodlands (Van Rensburg et al 1999;Van Rensburg et al 2000b;Botes et al 2006;.…”
Section: Introductionmentioning
confidence: 99%